Fourier transform and distributional representation of the gamma function leading to some new identities - M. Aslam Chaudhry; Asghar Qadir (International Journal of Mathematics and Mathematical Sciences)
We present a Fourier transform representation of the gamma functions, which leads naturally to a distributional representation for them. Both of these representations lead to new identities for the integrals of gamma functions multiplied by other functions, which are also presented here.